Using IoT Mesh Networks to Extend Wireless Coverage in Industrial Environments - Aquino, Carlos; Braga, Mozar; Carvalho, Vanessa; Moura, Evellin; Oliveira, Yanne; Gomes, Rafael Lopes (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC), 2023)
The rise of the Internet of Things (IoT) has led to the development of tailored intelligent ecosystems, where the Industrial Internet of Things (IIoT) has gained attention for its distinct needs. IIoT relies on seamless machine interaction through industrial wireless communication, but existing technologies like Zigbee and BLE may not meet its coverage, throughput and latency requirements. WiFi (IEEE 802.11) offers advantages to deal with these issues, but it faces challenges in industrial settings such as signal obstruction and interference, which can lead to coverage gaps and, consequently, performance issues. Within this context, this paper deploys IoT Mesh Networks with IIoT devices to improve the wireless coverage of industrial environments. Our IoT Mesh solution was developed using ESP32s devices and the experiments have followed a real testbed, evaluating the data transfer, throughput, delay, and loss, while varying the number of hops in the mesh backbone and the packet size.